Argumentation of the choice of the method of standardization of weekly physical activity for students with special health needs - Evseev S.P.; Shelekhov A.A.; Nenakhov I.G.; Grachikov A.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study. The purpose of this study is to establish a methodology for developing weekly physical activity standards for school students with sensory and intellectual disabilities. Methods and structure of the study. In the course of the work, a detailed analysis of the available analytical materials and reports was carried out, existing recommendations and instructions regarding the volume of physical activity of schoolchildren were investigated. With the help of questionnaires of children, their parents and specialists, the peculiarities of their behavior were revealed. Based on a comparison of the data obtained, an experiment was conducted to collect empirical information about the actual weekly motor activity of school-age children. Based on the analysis of the results obtained, an approach to the formation of weekly physical activity standards for schoolchildren of various age and nosological groups was proposed. Results and conclusions. Summarizing the preliminary results on the substantiation of the standards of weekly motor activity of children aimed at ensuring the health and developmental effect of physical culture and sports, in order to adjust the existing standards, we formulate the requirements for the content of the new standards. The key requirement is the mandatory integration of effective (priority), procedural and substantive parameters, which should be reflected in the standards. The approach proposed by the developers to setting standards for children’s motor activity, based on monitoring individual dynamics of physical fitness indicators, not only ensures the registration of qualitative changes, but also avoids large-scale biomedical research, which indicates its scientific validity and economic benefits.